Preliminary Overview of Several Capital Relocations in Relationship with a Plan of Indonesian Capital Relocation - Abd Muluk bin Abd Manan; Hitapriya Suprayitno (Journal of Infrastructure & Facility Asset Management, 2020)
A plan to move the Indonesian capital from Jakarta to Kalimantan island has been decided. Socialization of this program has been done by the government. A contest for the urban capital plan has been organized. But the Basic Systematic Reflection on Capital Relocation has never been developed among the academician. This development should be started by observing Capital Relocation Experiences. Six capital relocations have been observed. The research indicates that relocate the national capital to a new location is not something uncommon or inappropriate. The majority reasons for the capital relocation are the old capital is already too dense, to balancing the development, or certain military reason. In general, the success of relocation is having a more appropriate capital city with a desired and controlled density. While, the general failure of capital relocation is uncontrolled development, thus becoming a dense city.